2011
DOI: 10.1111/j.1537-2995.2011.03095.x
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in transfusion biology: identification and significance of mediators of morbidity and mortality in stored red blood cells

Abstract: Red cell transfusions are associated with inflammation and thrombosis, both arterial and venous, the mechanisms of which are not understood. Although a necessary life saving procedure in modern medicine, transfusions have rarely been subjected to modern assessments of efficacy and safety, including randomized trials. Storage of red blood cells induces changes, including the release of free hemoglobin and the accumulation of biologically active soluble mediators and microparticles. These mediators likely play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 63 publications
1
55
0
5
Order By: Relevance
“…However, despite leukoreduction, alloimmunization continues in RBC transfusion recipients. RBC-free hemoglobin and lipid mediators accumulate in microparticle and supernatant fractions of leukoreduced stored RBCs; moreover, apoptosis and loss of viability of residual white cells in leukodepleted units release immunostimulatory antigens, and mediators can sensitize the recipients [20,21]. In our study, the units transfused are non-leukoreduced, only neonatal and hematooncology patients received some leukoreduced hemocomponents.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite leukoreduction, alloimmunization continues in RBC transfusion recipients. RBC-free hemoglobin and lipid mediators accumulate in microparticle and supernatant fractions of leukoreduced stored RBCs; moreover, apoptosis and loss of viability of residual white cells in leukodepleted units release immunostimulatory antigens, and mediators can sensitize the recipients [20,21]. In our study, the units transfused are non-leukoreduced, only neonatal and hematooncology patients received some leukoreduced hemocomponents.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model, results showed that perfusion of rat lung with 42-day old purified lysophosphatidlcholine led to significant pulmonary edema and lung injury in LPS-primed rats. The investigators further demonstrated that infusion of a mixture of four non-polar lipids purified from 42-day old leukoreduced RBC from healthy volunteers induced lung injury in LPS-treated rats, but 1-day lipid solution did not [47].…”
Section: Rbc-derived Lipidsmentioning
confidence: 99%
“…These RBC membrane-derived MVs have more recently been shown to have physiologic and pathophysiologic significance by playing a role in inflammation and vascular dysfunction [47]. Cardo et al [48] assessed the neutrophilpriming ability of washed and unwashed RBCs stored for different durations and specifically the role of micro vesicles in priming neutrophils in vitro.…”
Section: Microvesiclesmentioning
confidence: 99%
“…These changes include changes to the cell shape and membrane, an increase in adhesiveness, a decline in flexibility (rigidity that can hamper blood flow hemodynamics), and reductions in capillary flow. [5][6][7][8][9] Further, older blood is associated with release of free iron that may predispose to vascular dysfunction, thrombosis, and nosocomial infections. [5][6][7][8][9] Finally, the storage medium could be deleterious by generating superoxides and inflammatory mediators that could result in oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Further, older blood is associated with release of free iron that may predispose to vascular dysfunction, thrombosis, and nosocomial infections. [5][6][7][8][9] Finally, the storage medium could be deleterious by generating superoxides and inflammatory mediators that could result in oxidative damage. [10][11][12][13] Observational studies, [14][15][16][17][18][19][20] although potentially confounded, 21,22 have suggested that these complicated mechanisms, often collectively referred to as "storage lesion," may adversely affect patient-important outcomes including infection, organ failure, hospital stay, and death.…”
Section: Introductionmentioning
confidence: 99%